2019
DOI: 10.3389/fphar.2019.00136
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by Sigma-1 Receptor of Morphine Analgesia and Tolerance: Nociceptive Pain, Tactile Allodynia and Grip Strength Deficits During Joint Inflammation

Abstract: Sigma-1 receptor antagonism increases the effects of morphine on nociceptive pain, even in morphine-tolerant animals. However, it is unknown whether these receptors are able to modulate morphine antinociception and tolerance during inflammatory pain. Here we used a mouse model to test the modulation of morphine effects by the selective sigma-1 antagonist S1RA (MR309), by determining its effect on inflammatory tactile allodynia (von Frey filaments) and on grip strength deficits induced by joint inflammation (a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…Earlier preclinical research had shown this modulatory role in the absence of chronic pain, using σ1 receptor knockout mice and σ1 receptor antagonists (Chien & Pasternak, ; Sánchez‐Fernández et al, ; Sánchez‐Fernández et al, ). Moreover, E‐52862 demonstrated efficacy restoring morphine analgesia in tolerant animals with acute nociceptive and inflammatory pain (Montilla‐García et al, ; Rodríguez‐Muñoz, Sánchez‐Blázquez, et al, ; Vidal‐Torres et al, ). Surprisingly, there were no previous studies assessing the role of σ1 receptors in modulation of opioid analgesia under conditions of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier preclinical research had shown this modulatory role in the absence of chronic pain, using σ1 receptor knockout mice and σ1 receptor antagonists (Chien & Pasternak, ; Sánchez‐Fernández et al, ; Sánchez‐Fernández et al, ). Moreover, E‐52862 demonstrated efficacy restoring morphine analgesia in tolerant animals with acute nociceptive and inflammatory pain (Montilla‐García et al, ; Rodríguez‐Muñoz, Sánchez‐Blázquez, et al, ; Vidal‐Torres et al, ). Surprisingly, there were no previous studies assessing the role of σ1 receptors in modulation of opioid analgesia under conditions of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, functional interactions have been reported between σ1 receptors and μ‐opioid receptors (Kim et al, ). Indeed, σ1 receptor antagonists enhance opioid‐induced analgesia in rodent models of acute nociception and inflammation (Chien & Pasternak, ; Montilla‐García et al, ; Vidal‐Torres et al, ) and did not potentiate opioid‐induced side effects such as tolerance or physical dependence (Vidal‐Torres et al, ), which could represent an important advantage for long‐term opioid treatment. However, it is not known if σ1 receptors modulate opioid analgesia and tolerance during osteoarthritis chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…The sigma-1 receptor was also a promising therapeutic target for the treatment of alcohol addiction [ 143 ], methamphetamine addiction [ 144 , 145 , 146 ], and cocaine addiction [ 147 , 148 , 152 ]. The sigma-1 receptor antagonist showed analgesic effects to relieve the symptoms in several peripheral neuropathy models [ 153 , 154 , 155 , 156 ]. MR309, a selective and novel antagonist of the sigma-1 receptor [ 164 ], has been tested in a phase II clinical trial, suggesting the promising action for oxaliplatin-induced peripheral neuropathic pain relief in patients [ 165 ]].…”
Section: The Sigma-1 Receptor-associated Diseasesmentioning
confidence: 99%
“…threshold force in mice when von Frey filaments are used is typically about 1 g (e.g. Montilla-García et al, 2019;Cobos et al, 2018), whereas an electronic device with a rigid filament yields a threshold of about 5-6 g (e.g. Nieto et al, 2012 and2014).…”
Section: The Development Of Pathological Pain Models and The Assessmementioning
confidence: 99%
“…This technique was recently adapted to study pain resulting from a variety of etiologies mostly affecting the limbs, such as muscle inflammation (Kehl et al, 2000 andSouza et al, 2018), muscle pain induced by repeated exercise (Fujiwara et al, 2017), musculoskeletal hyperalgesia induced by stress (Goudie-DeAngelis et al, 2016), bone cancer (Kehl and Fairbanks, 2003;Wacnik et al, 2003), osteoarthritis (e.g. Chandran et al, 2009;Honore et al, 2009;Lee et al, 2011;Hinata et al, 2018), inflammatory joint pain (Montilla-García et al, 2017;Dutta et al, 2018;Montilla-García et al, 2019), osteoporosis (Suzuki et al, 2018), and a model of sickle cell disease (Calhoun et al, 2015), among others. Grip strength deficits have also been observed during discogenic back pain (Millecamps et al, 2015;Millecamps and Stone, 2018;Yang et al, 2018), indicating that this outcome may be useful to detect pain even if the injury is not located in the limbs.…”
Section: Grip Strength Deficits As a Measure Of Pain-induced Functionmentioning
confidence: 99%